A NEW SPECIES OF HETEROSMINTHUS (DIPODIDAE, RODENTIA, MAMMALIA) FROM THE MIOCENE OF THE BAIKAL REGION - Lopatin A.V. (My University, 2001)
Based on fragmentary jaws from the Aya Cave (Baikal Region, Eastern Siberia; Middle Miocene) Heterosminthus erbajevae sp. nov. (Lophocricetinae, Dipodidae) is described. Based on the structure of the upper molars, the new species is closely related to the Central Asian lineage H. mongoliensis-H. orientalis, and is distinguished from the latter by the structure of M1. As the specimens are well preserved, the jaw morphology of Heterosminthus has been examined in detail.
Keywords: Miocene; Baikal Region; Heterosminthus erbajevae; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен